Efficacy and safety of сepeginterferon alfa-2b in double treatment regimen (cepeginterferon alfa-2b and ribavirin) of antiviral therapy in patients with chronic hepatitis C genotypes 2 and 3. Experience of real clinical practice - A. I. Pavlov; S. M. Kirillov; D. S. Ponomarenko; A. K. Havanshanov; J. V. Fadina; I. V. Bobkova; V. I. Vasenko; G. A. Volodina; T. Yu. Kulikova; Yu. N. Linkova; M. A. Morozova (Журнал инфектологии)
The objective: to analyze the experience of use of cepeginterferonalfa-2b and ribavirin in patients with chronic hepatitis C genotypes 2 and 3 in clinical practice, to evaluate the efficacy, safety and tolerability of this treatment regimen.Materials and methods. From 2013 to 2016 a total of 73 patients with chronic hepatitis C (CHC) received antiviral therapy with cepeginterferon alfa 2b (cePEG-IFN alfa-2b) and ribavirin in the Center for Gastroenterology and Hepatology of FSBE «Vishnevsky Third Military Clinical Hospital» of Russian Ministry of Defence. Treatment efficacy was assessed by the rate of sustained virologic response (SVR) on 24 week after completion of antiviral therapy. All cases of deterioration of the patient’s condition and laboratory abnormalities were registered throughout the treatment period and follow up. Severity of adverse events was assessed in accordance with the classification of CTCAE (Common Terminology Criteria for Adverse Events).Results. 73 CHC patients genotype 2/3 received cePEGIFN alfa-2b 1.5 μg/kg/week and ribavirin 800-1400 mg/day based on body weight for 24 weeks. SVR 24 was registered in 94,7% (n=54) of patients with HCV genotype 3 and in 93,7% (n =15) patients with genotype 2. During the first 12 weeks of therapy the normalization of serum transaminase activities was registered. All adverse events were typical for interferon/ribavirin treatment regimen.Conclusion. According to our data the use of double treatment regimen (CePEG-IFN alfa-2b and ribavirin) is reasonable in patients who don’t have negative predictive factors of response to IFN-based therapy. The SVR rate in this group of patients was 94.5%.